Diseño de una guía metodológica del sistema electrónico para la Contratación Pública -SECOP II- al proceso de Gestión Contractual en la Gobernación de Boyacá. (2022)
Technological tools such as SECOP II are a state strategy to increase the efficiency, transparency and traceability of public procurement, however, its operation depends on the correct generalized application in all public entities, which is why the transition towards the increasingly frequent use of the platform has been promoted, thus, of a mandatory nature for state entities,